Central types of convex fragments of the perfect Jonsson theory - Yeshkeyev, A.R.; Omarova, M.T. (Bulletin of the Karaganda University. Mathematics Series, 2019)
In this paper, the central types of convex fragments of the perfect Jonsson theory are considered. The main goal of this paper is to redefine the A.D. Taimanov’s question for complete theories in the sphere of Jonsson fragments of formula -definable subsets of a Jonsson fixed theory’s semantic model. Also the relationships between the center and Jonsson theory in the permissible enrichment of signature are considered. Herewith, the considered theories are hereditary. It is also assumed that an algebraic closure coincides with a definable closure. Within the framework of the above restrictions for the considered Jonsson theory, results on the existence of core models for such theories were obtained.